An engineering model for creeping flame spread over idealized electrical wires in microgravity - Coimbra, Alain; Li, Yutao; Guibaud, Augustin; Citerne, Jean-Marie; Legros, Guillaume; Consalvi, Jean-Louis (Comptes Rendus. Mécanique)
Flame spread over an insulated electrical wire is a major source of fire scenario in a space vehicle. In this work, an engineering model that predicts the creeping flame spread over cylindrical wires in microgravity is developed. The model is applied to interpret experimental data obtained in parabolic flights for wires composed by a 0.25 mm radius nickel-chromium (NiCr) metallic core coated by low-density polyethylene (LDPE) of different thicknesses ranging from 0.15 mm to 0.4 mm. The model relies on the assumption that, in the pyrolysis region, the NiCr and the LDPE are in thermal equilibrium. This assumption is supported by more detailed numerical simulations and the model reduces then to solving the heat transfer equations for both NiCr and LDPE in the pyrolysis region and in the region ahead of the flame front along with a simple degradation model for LDPE, an Oseen approximation of opposed oxidizer flow and an infinitely fast gas-phase chemistry. The flame spread rate (FSR) is controlled by two model parameters, which are measurable from intrinsic material and ambient gas properties: the convective flame heat flux transferred to the solid ahead from the flame front and the gaseous thermal heat length near the flame front. These parameters are then calibrated from experimental data for a given wire geometry and the calibrated model is validated against experimental data for other wire geometries and ambient conditions. The heat transfer mechanisms ahead of the pyrolysis front are investigated with a special emphasis on the LDPE thickness and the conductivity of the metallic core. In addition to NiCr, metallic cores of lower and higher conductivities are considered. The polymer is shown to be thermally thick for all tested wire geometries and core conductivities. The flame heat flux is found to dominate the heat transfer in the preheat zone where it applies. The core has nevertheless a significant impact in the heating of the LDPE with its contribution increasing with the core conductivity and when decreasing the LDPE thickness.